Medical students’ attitudes towards the clinical importance of embryology - Naureen Waseem; Khadija Iqbal; Noreen Anwar; Irum Rehman; Hina Kundi; Abdullah Qamar (Journal of the Pakistan Medical Association, 2021)
Objective of study: The objective of the study is to identify the attitudes of medical students towards the clinical importance of embryology. Methodology: The cross-sectional questionnaire-based survey was conducted at a private medical college of Sialkot, Islam Medical College from September 2019 to November 2019. Ethical approval was obtained from the Institutional Research and Ethics Committee prior to the study. Hundred First year and 100 final year medical students of Islam Medical College, participated in the survey. Thurdstone and Chave attitude analysis scoring was used to assess the attitudes. The questionnaire consisted of 20 statements. Students had to tick only those statements with which they were in full agreement. Prior to conducting the study a median score was taken out of 50 anatomy teachers, showing their opinion toward each statement. Results: The results of the study showed that the medical students do appreciate the importance of embryology in the early years and to a more extent in the clinical years. The attitude scores remained on the positive side. Female students showed better attitudes towards embryology in both years. Conclusion: To understand the importance of embryology efforts are required by the teachers teaching anatomy, and medical educationalists, to inform medical students of the relevance of embryology in attaining clinical competence. Key words: Attitude, Clinical, Embryology, Continuous...